Incidence of deep vein thrombosis following hip fracture survery at Tribhuvan University Teaching Hospital - Pokharel, Bishnu; Poudel, Sharma; Shah, Lakhan Lal (Journal of Chitwan Medical College, 2018)
Introduction: The incidence of venous thromboembolism (VTE) in Western population undergoing major orthopaedic surgery without any thromboprophylaxis has been reported to range from 32% to 88%. Recent studies done in Asian population however show variable results ranging from 5% to 50%. No study has yet been done to determine incidence of deep vein thrombosis (DV T) in Nepalese population. The objective of our study was to determine the incidence of DV T following hip fracture surgery.Methods: This was a prospective descriptive study of 66 patients of 40 years and above who had undergone hip fracture surgery admitted under the Department of Orthopaedics and Trauma Surgery, TUTH, Kathmandu, Nepal. Following hip fracture surgery, screening for the evidence of DV T was done on 5th postoperative day with Doppler ultrasonography of bilateral lower limbs.Results: The incidence of deep vein thrombosis in our study was 8% (5 of 66 patients) in the fractured limb. Three of them were distal DV T and 2 were proximal. None of the patients developed DV T in the unaffected limb.Conclusion: The incidence of deep vein thrombosis following hip fracture surgery is less in Nepalese patients. Thrombo-prophylaxis can thus be individualized according to other risk factors rather than use routinely in patients with hip fracture.